A novel formula for predicting the ultimate compressive strength of the cylindrically curved plates - Do Kyun Kim; Andy Ming King Wong; Jinha Hwang; Shen Li; Nak-Kyun Cho (International Journal of Naval Architecture and Ocean Engineering)
''The present study aims to develop an empirical formula to predict the ultimate compressive strength of unstiffened cylindrically curved plates. Drawing from an extensive analysis of 400 unique curved plate scenarios under longitudinal compression, we investigated critical parameters: the flank angle (denoted as θ), plate aspect ratio (denoted as a/b), and plate slenderness ratio (denoted as β). The ANSYS Nonlinear Finite Element Method (NLFEM) was employed to assess each scenario, considering the average level of initial imperfections (denoted as 0.1β2t) and configurations of one-bay and one-span. It is important to note that the models were designed without accounting for the effects of residual stresses. The simulation data generated from this analysis served as the foundation for developing our empirical formula. The proposed formula strongly agreed with the numerical simulations and experimental test results. This research provides structural engineers with a reliable predictive tool, aiding in more accurate predictions of the ultimate limit state (ULS) of curved plates during early design phases.